Implementasi Pembelajaran Islam Moderat Berbasis Kearifan Lokal di SMK Madura - Yulistiani, Yulistiani; Shohib, Muhammad (Universitas Nurul Jadid, 2025)
This study investigates how moderate Islamic education is implemented through local wisdom at SMK Az-Harul Ulum at SMK Az-Harul Ulum Gunung Rancak. The significance of this research is grounded in The urgency of promoting moderate Islamic education in Madura stems from the need to counter rising ideological rigidity and preserve the region’s strong tradition of tolerance and local wisdom and intolerance, as well as the role of local wisdom in strengthening students’ cultural identity and character. This study employs a qualitative approach with a case study design. with 10 teachers and 25 students from March to June 2024 with teachers, students, and school administrators, as well as through analysis of curriculum documents and learning materials. The data analysis technique used is thematic analysis to identify patterns and meanings within the collected data. The results of this research are expected to provide a comprehensive understanding of the implementation of the learning model, its challenges and supporting factors, as well as its impact on students’ understanding and internalization of moderate Islamic values and local wisdom at SMK Az-Harul Ulum Gunung Rancak. This research has the potential to contribute to the development of a model of moderate Islamic education that is relevant to the local cultural context.